Pengaruh Modifikasi Permainan Softball Terhadap Pembelajaran Siswa Inklusi - Achmad Zakaria; Raditya Pratama; Abdul Khasan (Pusat Riset dan Inovasi Nasional, 2022)
In general, education functions to develop abilities and shape the character of a dignified national civilization in order to make the nation's life more intelligent, aimed at developing the potential of students to become human beings who believe and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative. , be independent, and become democratic and responsible citizens. One of these subjects is physical education, sports and health. In learning activities, interaction between students and educators is needed so that learning is more active. So that learning can run actively and not be boring, it is necessary to implement new innovations provided by teachers so that students can increase their learning motivation to take part in physical education, sports and health lessons. One of them is by implementing modifications to the softball game that are adapted to the curriculum in the educational unit. The aim of this research is. Knowing the effect of softball game modifications on the learning motivation of inclusive students in PJOK learning in class VII of SMP Negeri 2 Karangpucung, Cilacap Regency. This research method uses a quasi-experimental research type, with a quantitative approach, and a one group pre-test post-test design. Data was collected using analysis techniques through motivation questionnaires. The target of this research was class VII inclusion students at SMP Negeri 2 Karangpucung, Cilacap Regency and the number of samples taken was 19 students. Based on the results of research that has been carried out and analyzed using SPSS (Statistics Product and Service Solution) version 25, it proves that the results of the hypothesis have no significant influence with a level of 0.191 > 0.05, strengthened by a Tcount value of 1.359